A comparison between family communication pre-pandemic and during pandemic among selected families in Metro Manila - Mendoza, Mariella B. (College of Home Economics, University of the Philippines Diliman, 2023)
This is a qualitative study that investigated different aspects of communication, specifically the changes in family communication that happened during the COVID-19 pandemic, the perceived effects of family communication on family relationships, the factors influencing it, and the level of satisfaction in family communication and family relationships among 10 purposively sampled parents and 10 child adolescents. Descriptive statistics and thematic analysis were used to summarize and analyze the collected data. Results show that the most noticeable changes that occurred during the pandemic were changes about the families’ topics of conversation, mode of delivery, and frequency of communication. The communication between parents and children were also found to be influenced by physical, personal, emotional, socio-cultural, and technological factors. Their communication also affects their relationships, as it enables members to express their needs, wants, and concerns; establishes a personal and deeper understanding among parents and children; creates a safe space for secrets and other confidential concerns; emphasizes the importance of family rules within the household; and allows management of conflicts between parents and children. Child adolescents were also found to be moderately satisfied with their family communication and very satisfied with their family relationships. On the other hand, parent respondents were slightly satisfied with their family communication and moderately satisfied with their family relationships. With the changes in communication during the pandemic that were determined, there is a need for families to maintain continuous effort and consistent practice in ensuring that their communication is effective and their relationship is satisfactory.